Development and Validation of RP-HPLC Method for Simultaneous Estimation of Emtricitabine and Tenofovir Disoproxil Fumarate in Bulk and Tablet Dosage Form - Dighe, Nachiket S; Shinde, Ganesh S; Magar, Sagar. D.; Deodhe, Ankita V. (Journal of Drug Delivery and Therapeutics, 2019)
An analytical method was developed for estimation of Emtricitabine and Tenofovir Disoproxil Fumarate in drug product by using high performance liquid chromatography. The chromatographic separation was performed on column Cosmosil C18 (250mm x 4.6ID, Particle size: 5micron) using methanol: water (70:30 v/v) as mobile phase with flow rate of 0.8 ml/min. The detection was carried by using UV-300-M detector at 266 nm wavelength. The retention times of Emtricitabine and Tenofovir Disoproxil Fumarate were found to be 3.561 and 5.478 min respectively. Run time was observed as 5.54 min and 7.05 min respectively for Emtricitabine and Tenofovir Disoproxil Fumarate. Validation was performed as per ICH guidelines which include accuracy, precision, linearity, specificity, LOD, LOQ, ruggedness and robustness all of these were found within standard range as per ICH norms. Preparation of mobile phase is very simple & does not require lengthy procedure. Proposed method was found to be accurate and specific for routine quality control of pharmaceutical dosage form like bulk and tablet dosage form.Keywords: Emtricitabine, Tenofovir Disoproxil Fumarate, HPLC, Validation.